2017
DOI: 10.1007/s10040-017-1553-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat tracing to determine spatial patterns of hyporheic exchange across a river transect

Abstract: Significant spatial variability of water fluxes may exist at the water-sediment interface in river channels and has great influence on a variety of water issues. Understanding the complicated flow systems controlling the flux exchanges along an entire river is often limited due to averaging of parameters or the small number of discrete point measurements usually used. This study investigated the spatial pattern of the hyporheic flux exchange across a river transect in China, using the heat tracing approach. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…A temperature probe (Figure 1b), which was equipped with thermistors on the metal tube, was inserted into the riffle downstream of the channel where no bridges or sharp bends were located, to measure the temperature of sediment at five different depths (0.0, 0.1, 0.2, 0.3, and 0.45 m) and hence, the temperature gradients were used to identify the patterns of hyporheic exchange [43]. Temperature measurements were recorded every 24 seconds by the data logger for approximately 30 min [44].…”
Section: Hyporheic Exchange Determinationmentioning
confidence: 99%
“…A temperature probe (Figure 1b), which was equipped with thermistors on the metal tube, was inserted into the riffle downstream of the channel where no bridges or sharp bends were located, to measure the temperature of sediment at five different depths (0.0, 0.1, 0.2, 0.3, and 0.45 m) and hence, the temperature gradients were used to identify the patterns of hyporheic exchange [43]. Temperature measurements were recorded every 24 seconds by the data logger for approximately 30 min [44].…”
Section: Hyporheic Exchange Determinationmentioning
confidence: 99%
“…Thermal parameters are considered constant in spatial and temporal distribution because of the relatively thermal homogeneity of streambed sediment. The values are determined through field observation, referring to several published studies [38,63,64].…”
Section: Analysis Methods Of Vertical Hyporheic Fluxmentioning
confidence: 99%
“…Schulz () compared fluxes estimated from Darcy calculations, multisensory temperature profiling and SBPVP, and found the temperature methods to produce estimates approaching a factor of 10 lower than the other methods—though variability in the Darcy calculations was highly dependent on the method used to estimate hydraulic conductivity. Although temperature‐based methods rely on a contrast between the temperature of groundwater and the temperature of surface water, which can vary seasonally (Krause and Blume ; Rose et al ), they have been shown to effectively quantify and delineate exchange zones in field studies (Westhoff et al ; Lu et al ).…”
Section: Introductionmentioning
confidence: 99%